2016
DOI: 10.1039/c6tb01792d
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity-controlled printing of supramolecular-polymeric hydrogels via dual-enzyme catalysis

Abstract: Hybrid hydrogels based on a guanidinium-containing oligopeptide are prepared via dual-enzyme-triggered reactions. An extended time window is available for in situ viscosity-controlled 3D printing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“… 103 105 Hydrogels based on reversible covalent bonds or supramolecular interactions are also promising to serve as printing materials for biomedical applications due to their self-healability at physiological conditions and multiresponsibility. 66 68 , 96 …”
Section: Applications Of Enzyme-regulated Healable Polymeric Hydrogelmentioning
confidence: 99%
See 2 more Smart Citations
“… 103 105 Hydrogels based on reversible covalent bonds or supramolecular interactions are also promising to serve as printing materials for biomedical applications due to their self-healability at physiological conditions and multiresponsibility. 66 68 , 96 …”
Section: Applications Of Enzyme-regulated Healable Polymeric Hydrogelmentioning
confidence: 99%
“…We have especially discussed the enzymatic fabrication of healable hydrogels and enzymatically regulated healing of hydrogels. In the studies on enzymatic fabrication of healable polymeric hydrogels, enzymatic reactions mainly play the roles of triggering the self-assembly, 60 , 66 polymerization, 60 , 66 , 67 , 70 and formation of reversible covalent bonds 68 , 69 in hydrogels. The dual-enzymatic self-assembly and polymerization is a valid strategy developed by Wang and co-workers for the preparation of self-healing polymeric hydrogels, and the resulting hydrogels have found applications in 3D cell printing and hemostasis.…”
Section: Conclusion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…22). [269] In these cases, enzymes are not directly involved in the cross-linking process, they are used as initiators for chain-growth polymerization. In that sense, enzyme-triggered free-radical polymerization cannot be properly considered as an enzyme-mediated cross-linking method.…”
Section: Enzyme-triggered Free-radical Polymerizationmentioning
confidence: 99%
“… 12 Other groups have employed an enzyme-trigger to switch-on an LMWG network. 13 Yang and co-workers demonstrated the ability of hybrid hydrogels to remain physically robust while extracting and releasing dyes from aqueous solutions, 14 then showed that a polymer additive could boost the anticancer activity of supramolecular LMWG nanofibres based on a taxol derivative. 15 Qi and co-workers developed hybrid hydrogels which incorporated taxol and achieved sustained release.…”
Section: Introductionmentioning
confidence: 99%